Physical Match Performance in Sub-elite Soccer Players – Introduction of a new Index - Reinhardt, Lars; Schulze, Stephan; Schwesig, Rene; Kurz, Eduard (International Journal of Sports Medicine, 2020)
This investigation examined the position-specific physical performance in different locomotor categories and physiological demands concurrently in official games of sub-elite players and to present a new performance index (PI). Time-motion (distance, velocity, acceleration) and heart rate data of 55 soccer players were simultaneously captured via a GPS tracking system. The relationship between external and internal match-load (PI) was determined on the basis of heart rate, average velocity and acceleration. In contrast to the mean heart rate (85.2±3.2%, P=0.806, ηp²=0.03), the average total distance covered (9946±715 m) was largely affected by players’ position (P<0.001, ηp²=0.63). Furthermore, a mixed design ANOVA showed a large interaction effect between position and locomotor category (P<0.001, ηp²=0.44). On average, PI was 1.57±0.37 m/min²/%, with notably lower values in the 2nd half. The position-specific profiles already reported for higher leagues were also present in sub-elite soccer players. Despite lower values for total distance and smaller distances in the high-intensity zones (>14.4 km/h), internal loads were comparable to those observed in European top leagues. In comparison to a performance measure that ignores accelerations, PI was shown to be less dependent on the playing position and had higher variability. Consequently, PI is better suited to distinguish between players’ performance.
Keywords: global positioning system; performance analysis; team sports; monitoring; wearable sensor